Surgical Correction of Congenital Diaphragmatic Hernias in Newborns Current Trends and Prediction of Results - Ramilevich Aubekirov, Artur; Sultanovna Shakieva, Milena; Yakubovna Chershembieva, Alina; Olegovna Goryanina, Nadezhda; Akhmednabievich Magomedov, Rashid; Nurlanovna Abuova, Safiya; Sayipovna Magomedova, Paizat (Journal of Neonatal Surgery, 2025)
The purpose of this study is to analyze current trends in the field of surgical correction of congenital diaphragmatic hernias in newborns, as well as to develop models for predicting treatment results, taking into account clinical, morphological and path physiological factors. The work is a combination of retrospective and prospective analysis based on data from a multidisciplinary hospital, where a comprehensive examination and treatment of newborns with congenital diaphragmatic hernias was carried out. During the study, the features of preoperative diagnostics, intensive care tactics, surgical techniques, as well as postoperative management of patients were considered. The results were analyzed taking into account the dynamics of vital functions, parameters of respiratory and hemodynamic support, as well as outcomes in the early and distant periods. The data revealed a number of factors affecting the success of surgical correction and the prognosis of survival. The use of modern minimally invasive methods, the use of new generation materials and the improvement of neonatal resuscitation significantly contribute to improving the immediate and long-term results of treatment. The developed prediction model allows more accurate assessment of the risks of surgery and personalized correction of treatment tactics, which in the future will reduce mortality rates and improve the quality of life of patients